2001
DOI: 10.1111/j.1745-4565.2001.tb00319.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Antimicrobial Drug Residues in Kenyan Milk

Abstract: The improved Dutch tube diffusion test was used to study the occurrence of inhibitory substances in raw bulk milk samples within the Nakuru District in Kenya. Initially the detection limits of the method were verified using milk standards spiked with selected antibiotics. Addition of penicillinase to inhibitor‐positive samples was used for preliminary identification of penicillin G‐type antibiotics and residue levels were estimated against a standard curve constructed by means of a B. stearothermophilus disc a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 2 publications
1
25
1
2
Order By: Relevance
“…Other positive cases were also found in cow milk (Bos taurus) in Trinidad, as mentioned by Adesiyun and Webb (20) , who found that 10.8% of samples were positive for antimicrobial residues. Moreover, Shitandi (21) reported that 21% of milk samples were also positive for antibiotic residues in Kenya, and according to Alomirah et al (22) , 5.4% of imported pasteurized milk samples and 3.4% of local pasteurized samples were positive for antibiotic residues in Kuwait. Another example is the one by Khaskheli et al (23) , who found that 37% of the samples were positive for Beta Lactam antibiotic residues in raw cow milk (Bos taurus) also in Pakistan.…”
Section: Discussionmentioning
confidence: 99%
“…Other positive cases were also found in cow milk (Bos taurus) in Trinidad, as mentioned by Adesiyun and Webb (20) , who found that 10.8% of samples were positive for antimicrobial residues. Moreover, Shitandi (21) reported that 21% of milk samples were also positive for antibiotic residues in Kenya, and according to Alomirah et al (22) , 5.4% of imported pasteurized milk samples and 3.4% of local pasteurized samples were positive for antibiotic residues in Kuwait. Another example is the one by Khaskheli et al (23) , who found that 37% of the samples were positive for Beta Lactam antibiotic residues in raw cow milk (Bos taurus) also in Pakistan.…”
Section: Discussionmentioning
confidence: 99%
“…al., 1999). In a previous study (Shitandi & Sternesjö, 2001) the tube test had been observed to have a good sensitivity with the method having an LOD of 1.5µg/Kg compared to the 2 µg/Kg Negative predictive value 95% 91%…”
Section: Discussionmentioning
confidence: 94%
“…Antibiotics residues in bovine milk are a problem in Kenyan milk (Ombui et al, 1995;Shitandi and Sternesjö, 2001). The β-lactam group of antimicrobials are in particular commonly utilised in lactating animals (Mandell and Perti, 1996;Mitchell et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Studies by Aning et al (2007) and Shitandi and Sternesjō (2007) indicate that the prevalence of antimicrobial residues in milk is relatively high in small scale dairy units where there is no adequate monitoring of withdrawal periods following use of antimicrobial agents in dairy cows. Therefore the need to monitor antimicrobial effects on fermentation of milk still exists.…”
Section: Discussionmentioning
confidence: 99%